Simulation And Analysis Of Compact Defected Microstrip Structure (DMS) With Narrow Bandwidth Notch Characteristics - Mutalib, Mohamad Ariffin; Zakaria, Zahriladha; Sam, Weng Yik; Awang Md Isa, Azmi (Penerbit Universiti, UTeM, 2014)
-